1995
DOI: 10.1145/204865.204889
|View full text |Cite
|
Sign up to set email alerts
|

LEDA: a platform for combinatorial and geometric computing

Abstract: Abstract. We give an overview of the LEDA platform for combinatorial and geometric computing and an account of its development. We discuss our motivation for building LEDA and to what extent we have reached our goals. We also discuss some recent theoretical developments. This paper contains no new technical material. It is intended as a guide to existing publications about the system. We refer the reader also to our web-pages for more information. What is LEDA?LEDA [MN95, MNU96] aims at being a comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(152 citation statements)
references
References 2 publications
0
148
0
4
Order By: Relevance
“…In this case only an approximation of the true minimum vertex cover is calculated, which is found to differ only by a few percent from the exact value. All methods have been implemented via the help of the LEDA library [32] which offers many useful data types and algorithms for linear algebra and graph problems.…”
Section: Rigorously Known Boundsmentioning
confidence: 99%
“…In this case only an approximation of the true minimum vertex cover is calculated, which is found to differ only by a few percent from the exact value. All methods have been implemented via the help of the LEDA library [32] which offers many useful data types and algorithms for linear algebra and graph problems.…”
Section: Rigorously Known Boundsmentioning
confidence: 99%
“…Though we highlighted an "Optical Circuit" for information processing and computation of even/odd parity circuit, we are not discussing in detail as such advanced topics like Photonics and Optical Computing, which deserve another research paper on an in-depth basis. Hence we are of the belief that our current research work is one of the pioneering efforts in this promising domain of Branching Programs which is interdisciplinary in nature (Mehlhorn & Nher, 1995;Moreinis, Morgenshtein, Wagner, & Kolodny, 2006;Morgenshtein, Fish, & Wagner, 2002;Morgenshtein, Friedman, Ginosar, & Kolodny, 2008;Nakano & Wada, 1998;Nishihara, Haruna, & Suhara, 1987;Okayama, Okabe, Kamijoh, & Sakamoto, 1999;Reed & Knights, 2004;Shi, Wa, Miller, Pamulapati, & Cooke, 1995;Isabelle, 2012;Anthony Fox, 2012; HOL: The Higher Order Logic Theorem Prover; Barrington's Theorem, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One can have similar branching programs for the parity function. It can be shown that every function on n bits can be computed by a branching program of width 3 and exponential length" (Hunsperger, 2002;Hussein, Nounou, Saada, Atef, & Khalil, 2006;Jang, Park, & Prasanna, 1992;Taki, 2000;Lattner, 2002;Mehlhorn & Nher, 1995;Moreinis, Morgenshtein, Wagner, & Kolodny, 2006;Morgenshtein, Fish, & Wagner, 2002;Morgenshtein, Friedman, Ginosar, & Kolodny, 2008;Nakano & Wada, 1998;Nishihara, Haruna, & Suhara, 1987;Okayama, Okabe, Kamijoh, & Sakamoto, 1999;Reed & Knights, 2004;Shi, Wa, Miller, Pamulapati, & Cooke, 1995;Isabelle, 2012;Anthony Fox, 2012; HOL: The Higher Order Logic Theorem Prover; Barrington's Theorem, 2009). Figure 1, we designed a simple boolean circuit and deduced its equivalent branching program, using the established mathematical and computational paradigms.…”
Section: Branching Program/s (Bp)mentioning
confidence: 99%
“…1 be drawn as a planar graph? We used an implementation [20] of the Leda [21] algorithms to test the planarity of the graph in Fig. 1 and found that it is not planar, since there is a K3,3 sub-graph whose nodes are (H, J, M) and (H-1, H-3, H-5).…”
Section: Topic Iconsmentioning
confidence: 99%